The Effect of Work Load and Burnout on Nurses on the Implementation of Patient Safety in Panembahan Senopati Hospital Bantul - herliansyah, Muhammd Faizal; ., Kusbaryanto; Hidayah, Nur (RA Journal of Applied Research, 2022)
Background: Nurses are medical personnel who have a big role in the hospital, The job descriptions of nurses are very large and time consuming. The workload that is owned is sometimes very large, causing Burnout, it is feared that the burnout will affect the implementation of patient safety. The purpose of this study is to determine the effect of burnout workload on nurses on the implementation of patient safety Methods: This research is a type of quantitative research that is observational with a cross-sectional design. Samples were taken from 6 wards, 54 nurses. Data analysis using kruskal-wallis. Results: The analysis showed that there was an influence between workload and implementation of patient safety (p = 0.029; p <0.05). The analysis showed that there was an influence between burnout and the implementation of patient safety (p = 0.033; p <0.05) Conclusion: there is a influence between burnout and workload on the implementation of patient safety on nurses at Panembahan Senopati Hospital, Bantul.